A new soil-dwelling palpigrade species from Northern Italy (Palpigradi: Eukoeneniidae) - Christian, Erhard (ZOOTAXA, 2009)
Among the 27 palpigrade species recorded in Europe so far, 23 occur in caves or narrow subterranean voids. Eukoenenia gallii n. sp. from a cork oak forest on the Italian Riviera (Liguria) is added to the small group of edaphic European palpigrades. E. gallii is not closely related to the common soil-dweller E. mirabilis (Grassi & Calandruccio, 1885), but to E. subangusta (Silvestri, 1903). Body shape and proportions make the new species look extremely edaphomorphic. All instars are described and illustrated with light micrographs of diagnostic traits.
Keywords: Arachnida; diagnostic characters; edaphomorphic; Eukoenenia; EUROPE; Liguria; taxonomy

Palaeovegetation from a Homo neanderthalensis occupation in Western Liguria: archaeopalynology of Madonna dell'Arma (San Remo, Italy) - Kaniewski, D; Renault-Miskovsky, J; de Lumley, H (JOURNAL OF ARCHAEOLOGICAL SCIENCE, 2005)
This study presents a short local vegetation history of Western Liguria (San Remo), northwest Italy, based on a palynological analyses of an 8.30-m-long archaeological section in the dune covering Madonna dell'Arma cave. Madonna dell'Arma is one of the Mousterian caves currently located on the Ligurian coastal zone. The site contains Levallois-type Mousterian tools, four pieces of skull attributed to Homo neanderthalensis and fauna remains belonging to Rhinoceros mercki, Elephas sp. and Hippopotamus amphibius. This study is of interest as the site is situated in an area where data on palaeovegetation. are scarce. In fact, the archaeopollen analyses of Madonna dell'Arma cave's surroundings provide a rare local picture of vegetation during the beginning of OIS 4, posterior to 73,100 yr BP. The palynological taxa are grouped into three vegetation units by PCA (principal components analysis). These data suggest a huge Mediterranean pre-steppic forest (Pinus, Quercus ilex and several herbs) colonizing the area during this substage. The adjacent valleys were colonized by a caducifoliate-alluvial forest and Mediterranean scrub vegetation. These vegetation characteristics suggest a semi-arid coastal climate with an increase of precipitation according to altitude. The PCA analyses of the palynological sections inside and outside the cave suggest a nearly continuous vegetation succession from OIS 5a to OIS 4. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: archaeopalynology; Italy; Liguria; Middle Palaeolithic; OIS 4; PCA

Santa Lucia superiore (Toirano, Ligurie) : reconstitution locale de la végétation ligure durant le Pléniglaciaire ancien - Kaniewski, David; Renault-Miskovsky, Josette; Tozzi, Carlo; de Lumley, Henry (Geobios, 2005)
Pollen analysis of Santa Lucia superiore cave (Italy) reports at local scale the lowland Ligurian vegetation during the Lower Pleniglacial (75 to 57 Kyr BP). The pollen proﬁle shows two AP extensions during a steppe-landscape episode in Liguria. The dry and cold phases caused the establishment of a steppe-landscape (NAP 92%) with Artemisia, Ephedra, Poaceae and Chenopodiaceae, similar to those mentioned in the Latium during the Pleniglacial. The increase of moisture generated a ﬁrst arboreal extension (Pinus, Betula, Corylus, Ulmus), which engendered the formation of an open-forest landscape (AP 43%). The second arboreal extension (AP 55%) was due to an increase of moisture and higher temperatures, which allowed the development of Mediterranean trees and shrubs (Quercus ilex, Olea, Phillyrea). This warming up occurred probably simultaneously with a secondary transgression during the glacial sea-level change. The upper part of the proﬁle shows an open vegetation, which indicates the return of a steppe-landscape. Pollen data, replaced in the multidisciplinary studies of the site, are well correlated with the fauna and sediment data.
Keywords: Full glacial; Liguria; Middle Palaeolithic; palynology; Prehistory; Upper Pleistocene

Madonna dell'Arma (San Remo, Italie) : expression locale de la végétation ligure au cours du Paléolithique moyen - Kaniewski, David; Renault-Miskovsky, Josette; de Lumley, Henry (Geobios, 2004)
Pollen analysis of Madonna dell’Arma cave inside part (Liguria, Italy) allowed us to reconstitute, at local scale, the Ligurian coastal vegetation between the end of the last interglacial period and the beginning of the pleniglacial. This transition period shows an important representation of arboreal cover and a persistence of thermophilous elements that allowed us to considerate the western Liguria as a periglacial refuge. During the end of the last interglacial, xerophytic, halophytic herbs and shrubs taken over from a Mediterranean pre-forest unit in the ﬁrst slopes constituted the coastal zone. The nearness ofArgentina torrent and theArmea inﬂuenced, in the coast, the existence of marshy zones colonized by hygrophilous trees. In the Ligurian lowlands spread out sclerophyllous and mesophilous forests according to altitude. The beginning of the pleniglacial is indicated in the sequence by increases of Pinus, Cupressaceae and Artemisia in the context of a decline in the thermophilous components. This picture of vegetation has become integrated into the multidisciplinary studies of the site and contributed to the elaboration of palaeoclimatic hypothesis similar as those revealed by the fauna.
Keywords: Interglacial; Liguria; Middle Palaeolithic; palynology; Pleniglacial; Prehistory; Upper Pleistocene